Hubungan Keaktifan Kegiatan Pondok Pesantren dengan Prestasi Belajar Siswa di MTs Al Hidayah Karangploso Malang - Shofi Rahmati; Ilyas Thohari; Ika Anggraheni (VICRATINA, 2019)
The background of this research is to find out how the learning achievements of students who take formal education and Islamic boarding school education, to find out how active students are in Islamic boarding schools and to find out the existence of a relationship between the activities of boarding schools and student achievement The activity of students in participating in activities in boarding schools can be one of the factors that can affect student learning achievement. By always being active in Islamic boarding school activities students will become accustomed to being active everywhere. This study is a type of quantitative research type of correlation with the subject of 42 students MTs Al Hidayah. The results of this study indicate a significant relationship between the activity of boarding schools and learning achievement.